2015
DOI: 10.1080/02755947.2015.1044626
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Responses of Fish to Habitat Enhancement in Barrenlands Streams of the Northwest Territories

Abstract: We examined the effectiveness of three fishpasses (two gabion‐style pool–weir fishpasses and one nature‐like choke‐and‐pool fishpass) at enhancing connectivity among three small, headwater lakes as part of a fish habitat compensation project in the Barrenlands region of the Northwest Territories. We quantified fish attraction and passage efficiency of fishpasses using PIT antennae, and compared fish use of fishpasses to reference streams using visual and electrofishing surveys for 1 year before and 2 years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Changes in water depths have been associated with large‐scale fish movements (Alabaster, ; Egglishaw & Shackley, ; Taylor & Cooke, ), and are often an important predictor of the probability to pass fishways (e.g., Cahill et al, ; Mallen‐Cooper & Brand, ). The probability to pass was positively correlated to water depth.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in water depths have been associated with large‐scale fish movements (Alabaster, ; Egglishaw & Shackley, ; Taylor & Cooke, ), and are often an important predictor of the probability to pass fishways (e.g., Cahill et al, ; Mallen‐Cooper & Brand, ). The probability to pass was positively correlated to water depth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Arctic Grayling often spawn in small streams during freshets (Northcote 1995;Stewart et al 2007), the onset of which is rapid, variable in timing among years, and of short duration (i.e., 5-10 d; Jones et al 2003a;Courtice et al 2014). Moreover, field observations suggested that Arctic Grayling appear in streams and fishpasses almost immediately after the freshet begins (Cahill et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the impacts of tagging mortality on our analyses, we analyzed passage events only from individuals that were detected in the M2S fishpass (as opposed to all tagged fish). Tagged Arctic Grayling that were detected as passing the fishpass were assumed to have been exposed to all conditions during the period of availability because M1L and M2L were small and because no tagged fish were detected as being present in or migrating through the M1S and M3S fishpasses (Cahill et al 2015). Environmental conditions associated with fish passage events were designated as "used," and we then created a matrix of available and used conditions for each fish.…”
Section: Arctic Grayling Fishpass Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nature-like fishways appear to be the most effective and promising mitigation strategy for fish passage (Franklin et al 2012;Steffensen et al 2013), there are no known studies of Rainbow Trout passage for this type of fishway design. In comparison, one study was conducted with Atlantic Salmon Salmo salar (Nyqvist et al 2017), one was conducted with Brook Trout Salvelinus fontinalis (Landsman et al 2018), five were conducted with Brown Trout Salmo trutta (Aarestrup et al 2003;Greenberg 2005, 2007;Tummers et al 2016;Dodd et al 2017), and 11 studies reported efficiency values for 43 nonsalmonid species at nature-like fishways (Schmutz et al 1998;Greenberg 2005, 2007;Franklin et al 2012;Steffensen et al 2013;Cahill et al 2015;Bunt et al 2016;Kim et al 2016;Landsman et al , 2018. Total efficiencies also varied greatly among these studies and ranged from 7% to 97% for salmonids alone, demonstrating both the design-specific and species-specific characteristics of fishway performance.…”
mentioning
confidence: 99%